2022
DOI: 10.1002/er.7919
|View full text |Cite
|
Sign up to set email alerts
|

Potential of molasses substrate for bioelectricity production in microbial fuel cell with the help of active microbial community

Abstract: The present study investigated the potential of different concentrations of molasses wastewater to produce bioelectricity, reduction of chemical oxygen demand (COD) and functionally active microbial community in microbial fuel cells (MFCs). Five different MFC setups were compared in which three were fed with molasses (two at room and one at 35 C temperature), while fourth and fifth were used as control reactors fed with distilled water and acetate, respectively. During first, second and third phases of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Plant residues in agricultural drainage sediments probably promoted the growth of these bacteria due to the SMFC's operation. Bhatti et al [73] reported that electricigens genus Romboutsia increased in microbial fuel cells with higher molasses and acetate, which might be a reason for the increased electricity production. The abundance of this genus would have supported electricity generation in our study.…”
Section: Changes In Microbial Communities In Smfcsmentioning
confidence: 99%
“…Plant residues in agricultural drainage sediments probably promoted the growth of these bacteria due to the SMFC's operation. Bhatti et al [73] reported that electricigens genus Romboutsia increased in microbial fuel cells with higher molasses and acetate, which might be a reason for the increased electricity production. The abundance of this genus would have supported electricity generation in our study.…”
Section: Changes In Microbial Communities In Smfcsmentioning
confidence: 99%